Studi Kasus Sistem Informasi Perawatan Dan Perbaikan Plafon Hotel Grasia Semarang - Hidayat, Fiqih Maulana; Astrianto, tegar Hari Abri; Junaidi, Junaidi (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2016)
The use of ceiling is increased with a growing era. This resulted in the need formaintenance and repair of the ceiling becomes very important. Therefore we need a system of information concerning the procedures for maintenance and repair of the ceiling. Information system that is less informative resulting ineffectiveness in the implementation of control maintenance and repair of the ceiling. Case studies will be a solution to overcome the problems of maintenance and repair of the ceiling with the scope of the maintenance and repair Acoustic ceiling and ceiling Gypsum. The goal is to facilitate the implementation of control and determination of maintenance and repair of the ceiling. This case study will provide information on how to maintain and repair the ceiling, determine the tools and materials, and determine the time of maintenance and repair of the ceiling in the Hotel Grasia Semarang